2023
DOI: 10.1038/s41537-023-00347-y
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thinning in relation to impaired insight into illness in patients with treatment resistant schizophrenia

Abstract: Impaired insight into illness is a common element of schizophrenia that contributes to treatment nonadherence and negative clinical outcomes. Previous studies suggest that impaired insight may arise from brain abnormalities. However, interpretations of these findings are limited due to small sample sizes and inclusion of patients with a narrow range of illness severity and insight deficits. In a large sample of patients with schizophrenia, the majority of which were designated as treatment-resistant, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Notably, it has been reported that patients with TRS exhibit widespread and stronger cortical alterations compared with patients with non-TRS [22][23][24][25]. Fan et al also reported that the cognitive impairment in the patients with TRS was largely mediated by cortical thickness of frontal, temporal, and parietal areas, suggesting cortical thinning might be associated with the pathophysiology of treatment resistance in schizophrenia and an important biomarker of those patients [26].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, it has been reported that patients with TRS exhibit widespread and stronger cortical alterations compared with patients with non-TRS [22][23][24][25]. Fan et al also reported that the cognitive impairment in the patients with TRS was largely mediated by cortical thickness of frontal, temporal, and parietal areas, suggesting cortical thinning might be associated with the pathophysiology of treatment resistance in schizophrenia and an important biomarker of those patients [26].…”
Section: Introductionmentioning
confidence: 99%
“…The cortical thickness has piqued the curiosity of researchers studying normal development and a wide range of neurodegenerative and mental illnesses-variations of the thickness of GM that can manifest in normal aging [23,24]. Cortical thinning is related to the atrophy of brain material, which can reveal much about the evolution and contributory factors of diseases [25], for example, Alzheimer's disease (AD) [26,27] and other dementias [27,28], Parkinson's disease [26,[28][29][30]], Huntington's disease [31,32], corticobasal degeneration [33,34], amyotrophic lateral sclerosis [35,36], and schizophrenia [37,38]. Multiple studies revealed that reduced cortical width is a sign of neurodegeneration associated with obesity, high body mass index (BMI), profound psychiatric illnesses, and AD.…”
Section: Introductionmentioning
confidence: 99%